Analysis of factors impacting corn grain basis values in Western Kansas - Wilson, Christian (Kansas State University, 2024)
Through the advancements of technology and demand, corn has become a foundational production crop for western Kansas producers. However, along with growth in corn production, corn price volatility also seems to be increasing at an increasing rate – especially since the growth in corn ethanol use began in earnest in 2006. The goal and scope of this study is to analyze variables impacting the local basis part of the cash grain pricing mechanism in Western Kansas. Variables considered in this study include historical weekly cash corn basis values, future values, price seasonality trends, the impact of ethanol biofuel corn usage, and state and national corn stock values. The geographical scope of the study is focused on Western Kansas, focusing on two key grain market locations, i.e., the Garden City Co-op in Garden City, in southwest Kansas, and Cornerstone Ag, LLC in Colby, in northwest Kansas. This study uses linear regression forecasting models to analyze and project the impact of key factors on corn basis levels. The data consists of weekly independent explanatory variables described above for marketing years from 2000 – 2022. The results of this model display the differing seasonality impacts, for both locations, along with market leadership for the Garden City grain markets in southwest Kansas in comparison to grain markets in Colby in northwest Kansas. Marketing years 2021/22 – 2021/22 were forecasted out-of-sample for both locations with known basis values to observe the accuracy of the model in comparison to historical five-year average basis values. These results determined that the lagged basis value from the previous week provides greater accuracy in determining the expected basis value for the next following week in comparison to historical five-year average basis values.
Keywords: Grain markets; Corn basis; Ethanol impact; Grain stocks; Western Kansas